2000
DOI: 10.1016/s0248-4900(00)88762-6
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and ultrastructural changes in Herpetomonas roitmani related to the energy metabolism

Abstract: Herpetomonas roitmani, a non-pathogenic trypanosomatid was grown in chemically defined media either containing proline or glucose as carbon source. Using transmission electron microscopy we observed that cells grown in the presence of proline present more lipid inclusions, and a larger mitochondrion with more cristae and higher activity of succinate cytochrome c reductase. On the other hand, cells grown with glucose as carbon source had more glycosomes, which were preferentially located close to the bacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…When the cells were grown in a medium containing glucose as the carbon source, glycosomes and mitochondria corresponded to a cell volume of 8.9 and 5%, respectively. However, when grown in the presence of proline, glycosomes and mitochondria accounted for 2 and 13.5% of the cell volume, respectively (Faria e Silva et al 2000). These observations show that there is a balance in the volume occupied by mitochondria and glycosomes in this species so that the total volume occupied by the two organelles corresponds to about 14% of the total cell volume.…”
Section: Organelles Involved In Metabolic Pathwaysmentioning
confidence: 70%
“…When the cells were grown in a medium containing glucose as the carbon source, glycosomes and mitochondria corresponded to a cell volume of 8.9 and 5%, respectively. However, when grown in the presence of proline, glycosomes and mitochondria accounted for 2 and 13.5% of the cell volume, respectively (Faria e Silva et al 2000). These observations show that there is a balance in the volume occupied by mitochondria and glycosomes in this species so that the total volume occupied by the two organelles corresponds to about 14% of the total cell volume.…”
Section: Organelles Involved In Metabolic Pathwaysmentioning
confidence: 70%
“…In T. cruzi amastigotes 3D reconstructions revealed the mitochondrion has a horse shoe shape [18, 66] while T. brucei trypomastigotes in the vertebrate host have a poorly developed branching mitochondrion [17, 35, 36]. Direct glycolysis may be used in the presence of high glucose concentrations (such as the blood) reducing the size of the mitochondrion between morphological forms and increasing the size of the glycosomes, which was observed in Herpetomonas roitmani [67] and T. brucei [20, 21] suggesting the parasites switch from oxidative phosphorylation to glycolysis. This process may reverse in the presence of low glucose environments such as the invertebrate gut resulting in a larger mitochondrion [22, 68].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to consider that ultrastructural and metabolic changes can be in¯uenced by growth conditions. Faria-e- Silva et al (2000) demonstrated changes in the relative volume of the mitochondrion in Herpetomonas roitmani, when cultivated under dierent growth conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative ultrastructural investigation in trypanosomatids has contributed to the understanding of their physiology (Brown and Vickerman 1973;Hecker 1974, 1975;Soares and De Souza 1988;Antoine et al 1989;Faria-e-Silva et al 2000). Previous studies have analyzed the ®ne structure of some Leishmania species during the process of promastigote±amastigote transformation (Tetley et al 1989;GalvaÄ o-QuintaÄ o et al 1990).…”
Section: Introductionmentioning
confidence: 99%